Assessing storage insect pests and post-harvest loss of maize in major producing areas of Ethiopia - Negasa Fufa; Tekalign Zeleke; Dawit Melese; Teshale Daba (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The survey was conducted for three years from 2018 to 2020 cropping seasons in four regions, Amahara, Oromia, SNNP and Benishangul Gumuz, to identify storage insect pests and to assess post-harvest loss of maize in major producing areas Ethiopia. All the collected data were analyzed by using the SPSS software and difference among means were also compared. A total of 280 farmers field were surveyed. 98% of the surveyed farmers used traditional storage structures. Sitophilus zeamais was occurred with a dominant mean number 120, 115 & 116 in Asosa, west Gojam & Hawasa areas, respectively. High mean 31.84% of grains damaged was recorded in the sample collected from Hawasa whereas, low mean 6.03% in the sample collected from Buno Bedele areas. High mean 18.00% of weight losses was recorded in the samples collected from Hawasa. The majority 64% of the surveyed farmers stored their grains for more than eight months. The mean number of weevils, weight loss and grain damage showed an increasing trend as the storage periods increased because of most of the farmers stored their maize with husk and/or unshelled in the house; store with cobs in bare ground which favors moisture development and temperature increment in the store. From this survey, it can be concluded that most of the surveyed farmers used traditional storage structures, stored their grains either shelled or unshelled, heap with stalk in the field for a longer period and used insecticides for the control maize weevils. These insecticides have harmful effect on the environment and human health. Therefore, uses of hermetic storage technology can be suggested to the farmers for, reducing weight loss, grains damage, use of insecticides and providing appropriate grains quality.